(3cJGH aj JGQjN GdYQH aj GdLGgdjIs
(3ChdgG (B:s
(3hLeYhG LeGLege aLYdhgG cGdche aSei gPG GdehVY OjQ GdLeGLe , hef QhGjI CHh Ydi GdbGdi Yf QLGdg , bGdhG (B: (3cGfJ EjGO deG fRdhG GdYQGb JZRhG Cgdg s
(3BNQgG (B:s
(3bGd gTGe (B: (3hbO QhjfG ai GdfNY hKbja , hai fRhdgceG efRdgeG HCHOGfgeG , MOjK BNQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1651/2) s
Keywords: (3GdJGQjNs